The Health Services White Paper : The Labour Party's policy
1944-09 1944 1940s 22 pages - 7 - (c) It is in competition with rather than in co-operation with the general practitioners. (d) It is usually very inadequately linked with the hospitals. The White Paper divides the clinics into two types; those which are functionally closely linked with the hospital and specialist services, and those which are not. The former type are placed under the new joint authorities. The latter remain under the existing local authorities, save that the school health services and the care of children from 2 years to school age go with the education services under the new Education Act. No one who has the efficiency of the health services at heart will quarrel with the first proposal. The second, however, is open to some objections. For example a mother will be looked after by one authority's clinics before and after the birth of her child; but the hospital in which she has her baby will be under another authority. Furthermore, the clinics remaining under the smaller authorities will have no links with either the specialist or the general practitioner service. The Labour Party therefore suggests that all the Clinic Services should be planned by or in association with the new Joint Authorities, and closely linked with the hospital services. IV. THE GENERAL PRACTITIONER SERVICE EXAMINED It has already been made clear why the Labour Party 1. Gives full support to the principle of a universally available service, 2. Reluctantly accepts the compromise of permitting doctors to treat patients privately for fees. 3. Considers that the general practitioner service should, like the hospital and specialist services, come under the new joint authorities. 4. Regards it as important that if a Central Medical Board for general practice is set up, its local area committees should cover the same areas as the new joint authorities. It goes without saying that - The Labour Party gives its full support to the principle of free choice of doctor. The other main points which call for consideration are:- The distribution of general practitioners The conception of Health Centres The conditions of work of general practitioners Their conditions of pay, and The sale and purchase of practices. 292/847/3/166